Control with uncertainty problems on the basis of fuzzy logic and the use of the hedge algebras in the knowledge -based system control. - Lân, Vũ Như; Hưng, Vũ Chấn; Phu, Đặng Thành; Châu, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2012)
-